Habitat disturbance and small mammal richness and diversity in an Atlantic rainforest area in southeastern Brazil Distúrbio no habitat e riqueza e diversidade de pequenos mamíferos em uma área de Mata Atlântica no sudeste do Brasil - C. F. Vera y Conde; C. F. D. Rocha (Brazilian Journal of Biology, 2006)
Since disturbance is an important ecological factor affecting species diversity in natural environments, the increasing human occupation rate in Brazilian Atlantic rainforest, which supports about 50% of Brazil's human population, has resulted in intense habitat degradation and fragmentation. Within this rainforest, animal and plant species have been lost at a high rate, and biological and diversity is presently vulnerable. Various animals community studies along a gradient of environmental disturbances have shown that the highest species diversities occur in habitats with intermediate levels of disturbance frequency and intensity. In the present study, which was carried out in the Atlantic forest of Ilha Grande (23° 11' S and 44° 12' W), an island located on the southern coast of Rio de Janeiro State, southeastern Brazil, we estimated species richness, diversity, and abundance of small mammals in three forest areas having different disturbance levels. This was done, in each of these areas and in an anthropic area that they surround, by establishing trails 200 m long, in which points were marked at 20 m intervals. The work involved a total effort of 4800 trap/nights. We also measured some habitat variables at each site in order to evaluated their disturbance levels. Our data showed that the two most conserved forests had the lower species richness and small mammal diversity, while in the anthropic area wild species were absent. The forest with an intermediary level of disturbance showed higher values for species richness and diversity, with the anthropic area presenting the highest disturbance level. Os distúrbios são importantes fatores ecológicos afetando a diversidade de espécies em ambientes naturais. Na Floresta Atlântica vive cerca de 50% da população humana do Brasil. A crescente ocupação humana neste ecossistema, resultou em uma intensa degradação e fragmentação do hábitat, tornando vulnerável a sua diversidade biológica e ocasionando uma alta taxa de perda de espécies animais e vegetais. Alguns estudos de comunidades têm demonstrado que ao longo de um gradiente de perturbação ambiental, os maiores valores de diversidade de espécies são encontrados em hábitats com níveis intermediários de frequência e de intensidade de distúrbios. No presente estudo, nós estimamos a riqueza, diversidade e abundância de espécies de pequenos mamíferos em três áreas de Mata Atlântica com diferentes níveis de distúrbio. O estudo foi conduzido na Mata Atlântica da Ilha Grande (23° 11' S e 44° 12' W), uma ilha localizada no Sul do estado do Rio de Janeiro, Sudeste do Brasil. Em cada uma das três áreas de florestas e em uma área antrópica rodeada por estas florestas, nós estabelecemos 10 trilhas paralelas com 200 metros de comprimento (com pontos a cada 20 m de intervalo e pontos adicionais acima do solo), num esforço total de 4800 armadilhas/noite. Nós também medimos algumas variáveis estruturais do hábitat para avaliar o nível de distúrbio em cada área. Nossos dados mostraram que as duas florestas mais conservadas tiveram os mais baixos valores de riqueza e diversidade de espécies e que na área antrópica ocorreu uma perda quase total de espécies silvestres. A floresta com nível intermediário de distúrbio teve os maiores valores de riqueza e diversidade de espécies, considerando a área antrópica como um hábitat sob alto grau de distúrbio.